2010
DOI: 10.1093/sleep/33.10.1285
|View full text |Cite
|
Sign up to set email alerts
|

Hypocretin and GABA Interact in the Pontine Reticular Formation to Increase Wakefulness

Abstract: underlies the pathophysiology of narcolepsy, 4,5 and disruption of hypocretin signaling in mouse, 6 rat, 7,8 and dog 9 leads to narcolepsy-cataplexy. Hypocretinergic neurons project to multiple areas of the brain, including those important for regulating sleep and wakefulness. 1 One such area is the pontine reticular nucleus, oral part (PnO). 1,10 The PnO is the rostral portion of the rodent pontine reticular formation 11 and contributes to the generation of wakefulness and rapid eye movement (REM) sleep. 12 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…In contrast, wakefulness is decreased and REM sleep is increased by pontine microinjection of GABA receptor antagonists or drugs that decrease GABA levels (Camacho-Arroyo et al, 1991; Xi et al, 1999, 2001; Sanford et al, 2003; Marks et al, 2008; Watson et al, 2008; Flint et al, 2010). Additionally, the increase in wakefulness caused by microinjecting hypocretin-1 into rat pontine reticular formation is blocked by coadministering the GABA A receptor antagonist bicuculline (Brevig et al, 2010). This finding supports the conclusion that in the pontine reticular formation, hypocretin-1 causes an increase in wakefulness by increasing GABAergic transmission (Watson et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, wakefulness is decreased and REM sleep is increased by pontine microinjection of GABA receptor antagonists or drugs that decrease GABA levels (Camacho-Arroyo et al, 1991; Xi et al, 1999, 2001; Sanford et al, 2003; Marks et al, 2008; Watson et al, 2008; Flint et al, 2010). Additionally, the increase in wakefulness caused by microinjecting hypocretin-1 into rat pontine reticular formation is blocked by coadministering the GABA A receptor antagonist bicuculline (Brevig et al, 2010). This finding supports the conclusion that in the pontine reticular formation, hypocretin-1 causes an increase in wakefulness by increasing GABAergic transmission (Watson et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo slice electrophysiology studies have shown that hypocretin increases firing rates of monoaminergic neurons in the LC, serotonergic neurons in the DR, histaminergic neurons in the TMN, and cholinergic neurons in the BF and LDT [5••], but have no effect on the GABAergic neurons in the VLPO. First reported by Brevig et al [24], injection of hypocretin-1 in a rat pontine reticular nucleus, a region involved in wakefulness and REM sleep, increases wakefulness that is mediated by GABAergic transmission of GABA A receptors. These findings indicate that activities of wake-promoting regions are without a doubt regulated by hypocretin.…”
Section: Hypocretin and Regulation Of Sleep/wakefulnessmentioning
confidence: 95%
“…With the assumption that OX2 receptors are coupled exclusively to G q proteins, a disinhibitory action through their presynaptic regulation of inhibitory GABAergic neurons might be a probable mechanism (Kukkonen et al, 2002). Studies have also suggested an excitatory role of OX2 receptors in modulating activity of GABAergic neurons in the medial septum/diagonal band of Broca (Wu et al, 2002) and arcuate nucleus (Burdakov et al, 2003), indicating that, at least in other brain areas, activation of OX2 receptors could result in an increase of GABA release and a subsequent inhibitory action on other neurotransmitters in the area via GABA A receptors (Nuñez et al, 2006;Brevig et al, 2010). An alternative mechanism could involve a direct action through OX2 receptors coupled to G i/o proteins and localized on cholinergic, histaminergic, and norepinephrinergic nerve terminals.…”
Section: Discussionmentioning
confidence: 99%